The Vital Role of the Laity in Revitalization: A Case Study of Misión Cristiana Elim - Danielson, Robert A. (The Asbury journal, 2014)
Immigration from Latin America to the U.S. is often seen as the movement of individuals across borders, but it often impacts communities as well, including religious organizations. Because of the cell-group focus of Misión Cristiana Elim in El Salvador and the large number of Salvadoran immigrants, it is not surprising that this movement is also growing rapidly as immigrants move into new areas. This case illustrates how one Hispanic church movement is growing transnationally through immigration.